Pulmonary Sequelae in Patients After Recovery From Coronavirus Disease 2019: A Follow-Up Study With Chest CT - Liao, Xuejiao; Li, Dapeng; Liu, Zhi; Ma, Zhenghua; Zhang, Lina; Dong, Jingke; Shi, Yirong; Gu, Xiaowen; Zheng, Guangping; Huang, Ling; Yuan, Lijun; Cao, Jing; et al. (Frontiers in Medicine, 2022)
Objective: The pulmonary sequelae of coronavirus disease 2019 (COVID-19) have not been comprehensively evaluated. We performed a follow-up study analyzing chest computed tomography (CT) findings of COVID-19 patients at three and six months after hospital discharge. Methods: Between February 2020 and May 2020, a total of 273 patients with COVID-19 at the Shenzhen Third People's Hospital were recruited and followed for six months after discharge. Chest CT scanning was performed with the patient in the supine position at end-inspiration. A total of 957 chest CT scans was obtained at different timepoints. A semi-quantitative score was used to assess the degree of lung involvement. Results: Most chest CT scans showed bilateral lung involvement with peripheral location at three months and six months follow-up. The most common CT findings were ground-glass opacity and parenchymal band, which were found in 136 (55.3%) and 94 (38.2%) of the 246 patients at three months follow-up, and 82 (48.2%) and 76 (44.7%) of 170 patients at six months follow-up, respectively. The number of lobes and the total CT severity score declined over time. The total CT score gradually increased with the increasement of disease severity at both three months follow-up (trend test P < 0.001) and six months follow-up (trend test P < 0.001). Patients with different disease severity represented diverse CT patterns over time. Conclusions: The most common CT findings were ground-glass opacity and parenchymal bands at the three months and six months follow-up. Patients with different disease severity represent diverse CT manifestations, indicating the necessary for long-term follow-up monitoring of patients with severe and critical conditions.